Implementation of Upin Ipin Song in Hijaiyah Letter Recognition in Children in Ra Sunan Bonang - Nuril Falina; Terza Travelancya D.P; Ivonne Hafidlatil Kiromi (Journal Of Social Science (JoSS), 2024)
This study aims to find out how the application of singing methods in introducing hijaiyah letters in early childhood group A in RA Sunan Bonang Brani wetan. The method used is a qualitative approach with descriptive analysis. The object of this study was as many as 16 people, with the techniques used by researchers in collecting data, namely observation, interview and documentation techniques. To analyze the data, researchers also use data collection, data reduction, data presentation and conclusions. The study was conducted for 1 month. The application of the method of singing with the song hijaiyah upin ipin is very effective in providing hijaiyah letter recognition to children from an early age in group A RA Sunan Bonang Brani wetan, with the steps used; Preparation and Planning of Learning Implementation of Singing Method, Teachers Understand Well the Material Teach, Selection of Songs to be Taught to Children, Demonstrate Songs Repeatedly, Convey Learning Information, Ask Questions. The impact of using this method is that children have an interest in learning hijaiyah letters and are involved in the learning process such as singing together and answering questions together (activ), the learning environment created also becomes fun, and children memorize faster so that it also makes it easier for children to recognize hijaiyah letters.